PENERAPAN GAME EDUKASI ULAR TANGGA SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN MINAT BELAJAR SISWA MADRASAH IBTIDAIYAH - Firdaus, Syahadatinah; Kholil, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the process of implementing the Snakes and Ladders educational game in mathematics learning and analyze the increase in student interest and engagement in length and weight measurement in fourth-grade students at Mambaul Hasan Islamic Elementary School. This study used a qualitative approach with a case study design. The subjects were all fourth-grade students at Mambaul Hasan Islamic Elementary School. Data collection techniques were conducted through observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that before the implementation of the educational game, learning was still dominated by lectures and practice exercises, resulting in students being passive, lacking focus, and having low learning interest. The use of learning media in teaching and learning activities can increase and stimulate interest and talent, increase student motivation, foster organized reasoning, reduce and avoid verbalism, and foster a systematic approach, while fostering positive values ​​in students (Ruhma & Hanik, 2023). Classes become more interactive, enjoyable, and student-centered. Student interest and engagement increased, as indicated by more focused attention, enthusiasm in participating in the game, active participation in group discussions, and courage in answering questions. Thus, it can be concluded that the implementation of the Snakes and Ladders educational game is effective in increasing student interest and engagement in mathematics lessons on length and weight measurement in fourth grade at MI Mambaul Hasan. The application of the Snakes and Ladders game can be combined with various models, as well as encouragement and rewards. In implementing this media, educators are expected to be innovative and creative in exploring the learning process in the classroom (Tazkiyah et al., 2025).